(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Electronic record management systems are essential for organizations to protect and improve their efficiency. They involve the professional practice of classifying, organizing, and managing documents and records. However, challenges faced by electronic record management systems include not have own username and password on their PC when it comes to using the system, outdated information systems, and having only one internet service provider in the company office that is used in the system. It is important for records professionals to perform the required scope of responsibilities when implementing the Records Management System program. Without a records specialist, the entire task would be difficult for untrained, inexperienced individuals to complete. The level of familiarity, usability and efficiency, accessibility, and effectivity are strongly agreed upon. Employees should record copies of documents and keep them on an official file, have a staff member in the record and archives office with assigned responsibility to use electronic document and transaction management systems (EDTMS), browse through available files or folders, and store permanent records with temporary records until they are transferred for archiving. Electronic record-keeping is essential for any business as it allows for the management of one of the most crucial resources in any organization. A policy must be developed to govern record management operations and ensure that all records generated and received are properly documented. Additionally, policies should be created and managed by documenting them, assigning roles, and developing formal processes. Finally, secrecy or restricting access to electronic records must be prevented, and users must be ensured that user records are highly safeguarded and monitored. The electronic records management life cycle idea must be utilized at all levels of the company, and an acceptable model for the preservation of records and data must have been developed.